Pengembangan Keterampilan Bahasa Reseptif Anak Usia Dini melalui Gerakan Ibu Membacakan Buku di Rumah - Rofika Irmanasari; Heru Kurniawan (Lembaga Yasin AlSys, 2026)
Although early childhood language development has been widely studied through various school-based learning approaches, studies that specifically discuss family-based literacy interventions through a structured movement integrated with early childhood education institutions remain limited. This study aims to analyze and describe the implementation of the Gerakan Ibu Membacakan Buku di Rumah in developing the receptive language skills of early childhood children. This study employed a qualitative approach with a field study design, involving 12 participants consisting of teachers and parents at PAUD Rumah Kreatif Wadas Kelir who were selected through purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the program was implemented in a structured manner through collaboration between the school and families, which had an impact on improving children’s receptive language abilities, including listening skills, language comprehension, vocabulary mastery, and retelling ability. These findings contribute to strengthening understanding of the importance of family-based literacy interaction in the context of early childhood education. The conclusion of the study emphasizes the importance of consistency in implementation, the quality of parent–child interaction, and synergy between schools and families in optimizing children’s language development. The practical implications of this study provide a basis for early childhood education institutions and parents in designing sustainable literacy programs and open opportunities for further exploration of more adaptive and contextual family-based literacy intervention models.